Psychophysical measures of visual function and everyday perceptual experience in a case of congenital stationary night blindness - Cammack J (Dove Medical Press, 2016)
Jocelyn Cammack,1 John Whight,2 Vinette Cross,3 Andrew T Rider,1 Andrew R Webster,1,2 Andrew Stockman1 1Department of Visual Neuroscience, UCL Institute of Ophthalmology, 2Moorfields Eye Hospital, London, 3Centre for Health and Social Care Improvement, University of Wolverhampton, Wolverhampton, UK Abstract: An appreciation of the relation between laboratory measures of visual deficit and everyday perceptual experience is fundamental to understanding the impact of a visual condition on patients and so to a fuller characterization of the disorder. This study aims to understand better the interpretative processes by which modified sensory information is perceived by a patient with congenital stationary night blindness and the adaptive strategies that are devised to deal with their measurable visual loss. Psychophysical measurements of temporal resolution, spectral sensitivity, and color discrimination were conducted on a 78-year-old male patient with the condition, who was also interviewed at length about the ways in which his diagnosis affected his daily life. Narrative analysis was employed to identify the relation between his subjective perceptual experiences and functional deficits in identifiable components of the visual system. Psychophysical measurements indicated a complete lack of rod perception and substantially reduced cone sensitivity. Two particular effects of this visual loss emerged during interviews: 1) the development of navigational techniques that relied on light reflections and point sources of light and 2) a reluctance to disclose the extent of visual loss and resulting lifelong psychosocial consequences. This study demonstrates the valuable complementary role that rich descriptive patient testimony can play, in conjunction with laboratory and clinical measurements, in more fully characterizing a disorder and in reaching a more complete understanding of the experience of vision loss. It also evidences the particular suitability of filmmaking techniques as a means of accessing and communicating subjective patient experience. Keywords: congenital stationary night blindness, GRM6 gene, narrative analysis, perception, psychophysics, quality of life